Learner Autonomy in Distance Learning: A Connection between Perceived Learner Autonomy and Academic Achievement in Distance Learning at the University of Iceland - Theodór Aldar Tómasson 1978- (2014)
The purpose for this study was to examine whether there was a connection between perceived learner autonomy and academic success in distance learning in the Department of English at the University of Iceland. Learner autonomy is the capacity to take charge of, responsibility for and control over one’s own learning. Learner autonomy includes abilities, attitudes and skills that people possess, and can develop to various degrees. They involve being independent, organized, motivated, goal oriented, having effective learning strategies, monitoring and assessing the effectiveness of their own learning practice. These are qualities that are important in being an autonomous learner and also a successful distance learner since being a distance learner involves learning on one’s own, being organized with time and schedule; display self – control and discipline when it comes to one’s own learning. Twenty distance and 31 on-site students from two content courses in the Department of English at the University of Iceland participated in a survey which determined how autonomous learners perceive themselves to be. The result from this survey was compared to the participants’ final grade in the content courses by using the Pearson Correlation Coefficient method to find out if there was any connection between perceived learner autonomy and academic success in distance learning. The results of the study suggest there is moderate correlation between the two variables, academic success and perceived learner autonomy, among the twenty distance students, while there is weak and low correlation in the relationship of the two variables, academic success and learner autonomy, among the on-site students. Therefore, the result suggests there is a connection between perceived learner autonomy and success in distance learning. Tilgangur þessara rannsóknar var að kanna hvort tengsl væru á milli nemendasjálfstæðis (e. learner autonomy) og árangurs í fjarnámi á námsbraut í ensku við Háskóla Íslands. Nemendasjálfstæði er getan til að stýra og ...